Safety and efficacy of magnesium-rich artificial cerebrospinal fluid for subarachnoid hemorrhage - Cheng, Yawen; Han, Xiangning; Xie, Wanfu; Xu, Gaofeng; Bai, Xiaobin; Qi, Lei; Zhang, Linjuan; Liu, Rui; Dong, Weihua; Feng, Weiyi; Pang, Chengsen; Zhang, Wei; et al. (Frontiers in Neurology, 2024)
Objectives: This study aimed to investigate the efficacy of using a newly formulated magnesiumrich artificial cerebrospinal fluid (MACSF) as an alternative to normal saline (NS) for intraoperative irrigation during aneurysm clipping in improving the prognosis of patients with Aneurysmal subarachnoid hemorrhage (aSAH). Methods: Patients with aSAH who underwent intraoperative irrigation with MACSF or NS during the clipping in the First Affiliated Hospital of Xi 'an Jiaotong University from March 2019 to March 2022 were selected as MACSF group and NS group, respectively. The primary prognostic indicators were the incidence of favorable outcomes (mRS 0-2). The secondary outcome measures included cerebral vasospasm (CVS), mortality, total hospital stay, and intensive care unit (ICU) stay. Safety was evaluated based on the occurrence rates of hypermagnesemia, meningitis, and hydrocephalus. Results: Overall, 34 and 37 patients were enrolled in the MACSF and NS groups, respectively. At 90 days after aSAH onset, the proportion of favorable prognosis in the MACSF group was significantly higher than that in the NS group (P=0.035). The incidence of CVS within 14 days after surgery was significantly lower in the MACSF group than that in the NS group (P=0.026). The mortality rate in the MACSF group was significantly lower than in the NS group (P=0.048). The median lengths of hospital stay (P=0.008) and ICU stay (P=0.018) were significantly shorter in the MACSF group than in the NS group. No significant differences were observed in safety measures. Conclusion: Using MACSF as an irrigation fluid for aneurysm clipping can significantly improve the 90-day prognosis of patients with aSAH, which may be related to the reduced incidence of CVS.